2020
DOI: 10.1093/glycob/cwaa099
|View full text |Cite
|
Sign up to set email alerts
|

Exploring lectin–glycan interactions to combat COVID-19: Lessons acquired from other enveloped viruses

Abstract: The emergence of a new human coronavirus (SARS-CoV-2) has imposed great pressure on the health system worldwide. The presence of glycoproteins on the viral envelope opens a wide range of possibilities for application of lectins to address some urgent problems involved in this pandemic. In this work, we discuss the potential contributions of lectins from non-mammalian sources in the development of several fields associated with viral infections, most notably COVID-19. We review the literature on the use of non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 155 publications
0
26
0
Order By: Relevance
“…On the other hand, we have demonstrated that SARS-CoV-2 surface N- glycans are essential for infection. New potential treatments may consist of blocking such glycans using antibodies or lectins to reduce and neutralize the spread of the infection 30 . Concerns are currently arising about new SARS-CoV-2 variants that could potentially escape treatments under development or vaccine-derived antibody neutralization.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, we have demonstrated that SARS-CoV-2 surface N- glycans are essential for infection. New potential treatments may consist of blocking such glycans using antibodies or lectins to reduce and neutralize the spread of the infection 30 . Concerns are currently arising about new SARS-CoV-2 variants that could potentially escape treatments under development or vaccine-derived antibody neutralization.…”
Section: Discussionmentioning
confidence: 99%
“…Table IV: The choice of lectin sensors as controls to improve confidence in data from aptamer tests. Non-mammalian lectins with anti-viral activities 586 (top). Use in biosensors (bottom).…”
Section: The Case For Lectin Sensors As Controlmentioning
confidence: 99%
“…The interaction with glycoproteins conjointly allows the use of lectins within the development of devices for identification and characterization of glycoproteins in a viral envelope or alterations in host glycoproteins throughout virus infection. Lectins are natural proteins that focus on the sugar moieties of a large vary of glycoproteins [10]. They are prevailing among higher plants and are divided into seven families of structurally and evolutionarily connected proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally to the antiviral impact of mannose-and N-acetylglucosamine-specific agglutinins on HIV, the associate repressive impact of those plant lectins was reported on respiratory syncytial viral infection, CMV infection, and influenza A virus infection in vitro. Carbohydrate-binding agents are thought of as anti-CoV agents that focus on spike protein and restrain CoV entry [10]. They're proficient to bind specifically with the oligosaccharides on virus surfaces like HIV and S glycoprotein.…”
Section: Introductionmentioning
confidence: 99%